Laser safety in the lab - Barat, Ken (SPIE, 2013)
There is no more challenging setting for laser use than a research environment. In almost every other setting the laser controls count on engineering controls, and human exposure is kept to a minimum. In research, however, the user often manipulates the optical layout and thereby places him or herself in peril, but this does not mean that accidents and injury are unavoidable. On the contrary, laser accidents can be avoided by following a number of simple approaches. Laser Safety in the Lab provides the laser user and laser safety officer with practical guidelines from housekeeping to eyewear to on-the-job training.
"SPIE Digital Library."--Website.
Keywords: Lasers -- Safety measures.; Laboratories -- Safety measures.; elektronické knihy; electronic books